Frequency of Genetic Polymorphism of the Gene Encoding 16kDa Clara Cell Secretory Protein (CC16) in Shiraz, Iran - M Saadat; DD Farhud (Tehran University of Medical Sciences, 2005)
The Clara cell protein (CC16) is a small and readily diffusible protein of 16 kDa secreted by bronchiolar Clara cells in the distal airspaces. Mutation detection methods identified an adenine to guanine substitution in the CC16 gene at position 38 (A38G) downstream from the transcription initiation site within the non-coding region of exon 1. In the present study, the genetic polymorphism of CC16 was detected by PCR-based method in 175 normal individuals from Shiraz population, Fars province (south of Iran). Initially the subjects were divided into two sex groups. Considering that there was no statistically significant differences between males and females (χ2 = 5.52; df = 2; P<0.05) the sex groups were pooled. The frequencies of 38A and 38G alleles were 0.24 and 0.76 percent, respectively. The study population was at Hardy-Weinberg equilibrium (χ2 = 2.61; df = 1; P<0.05). The present results indicated that this polymorphism might have a geographic distribution.